Design of Performance Measurement System in Feed Company PT XYZ With Balance Scorecard Approach - Dedi Kurniadi; Idqan Fahmi; Tanti Novianti (Universitas Tidar, 2022)
The management of PT XYZ realizes that the company needs another method that is able to comprehensively provide views with various approaches to corporate strategy formulation. Management is very aware that even though the company has been established for more than 30 years, there are several conditions that need to be improved including 1) Data that is still not integrated, where data from each department is still collecting, managing and utilizing data related to departments and not free to obtain data support from the department easily. 2) The company does not yet have appropriate indicators to develop and manage a sustainable business. and 3) The company does not yet have an integrated approach in viewing all important aspects of the business. This study aims to obtain comprehensive measurements and analyze benchmarks with a balanced scorecard. The data used were primary through interviews and secondary data with literature studies. The methods used were descriptive, paired comparison and BSC analysis. The results show that using the BSC is able to provide a comprehensive and appropriate picture of 4 perspectives